Professor do ensino superior : discutindo as necessidades de formação pedagógica - Carreño, Leidne Sylse S. de Mello (2011)
This study aims to consider and discuss the need for pedagogical training for university teachers based on the expressions of a group of teachers who work at the Federal University of Pelotas. The line of though used looks upon the perceptions of the interviewees about their education and the challenges they face in teaching. Considering that there is reasonable consensus that to be a university professor is suffices to dominate the knowledge of their area and little appreciation is given to the nature of pedagogical knowledge. The data were collected through semi-structured interviews applied to a sample of six teachers from the courses of Architecture and Urbanism and from Dentistry. The results were analyzed in the light of the theoretical Zabalza (2004), Marcelo Garcia (1999), Cunha (2000, 2004 ), Masetto, (1998, 2009), , Pimenta and Anastasiou (2002), among others. The results helped us to understand that even if the professionals working in higher education are trained in Master and/or PhD, they are still unprepared to face the complexity of teaching. We also realize that these professionals become teachers and still need some time before identifying themselves as a "teacher"